2017
DOI: 10.4314/tjpr.v16i6.29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and awareness of anabolic androgenic steroid use among male body builders in Jazan, Saudi Arabia

Abstract: Purpose: To examine the prevalence and awareness of anabolic-androgenic steroid (AAS) use among male bodybuilders visiting gyms in Jazan region, Saudi Arabia. Methods: A cross-sectional survey was conducted among 500 male bodybuilders visiting gyms in the Jazan region of Saudi Arabia. Information on demographics, as well as the use of AAS, was included in a self-administered questionnaire. Results: The prevalence of AAS in Jazan was 31.0 % (95 % CI,, and it was higher among those in the [30][31][32][33][34]. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 22 publications
(33 reference statements)
3
37
2
3
Order By: Relevance
“…We included published empirical records on AAS from searches in the twenty-one countries located in the Eastern Mediterranean region. The types of records included were survey studies in Saudi Arabia (Al Bishi and Afify 2017; Al Al Nozha and Elshatarat 2017;Alharbi et al 2019;Althobiti et al 2018;Bahri et al 2017;Jabari et al 2016), United Arab Emirates , Kuwait Alsaeed and Alabkal 2015;Khullar et al 2016), Iran (Allahverdipour et al 2012;Angoorani and Halabchi 2015;Asr et al 2018;Bordbar et al 2014;Fijan et al 2018;Haerinejad et al 2016;Jalilian et al 2011;Kargarfard et al 2015;Mohammad 2014;Nakhaee et al 2013;Razavi et al 2014;Rezaei 2017;Saeidinejat et al 2017;Sepehri et al 2009;Sobhanian et al 2013), Iraq Habeeb et al 2012), Lebanon Melki et al 2015), Jordan Wazaify et al 2014), Pakistan Uddin et al 2019;Zafar et al 2018), and Sudan (Khidir and Mahmoud 2018); and conference proceedings from Bahrain ) (see Table 2). Correlational study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We included published empirical records on AAS from searches in the twenty-one countries located in the Eastern Mediterranean region. The types of records included were survey studies in Saudi Arabia (Al Bishi and Afify 2017; Al Al Nozha and Elshatarat 2017;Alharbi et al 2019;Althobiti et al 2018;Bahri et al 2017;Jabari et al 2016), United Arab Emirates , Kuwait Alsaeed and Alabkal 2015;Khullar et al 2016), Iran (Allahverdipour et al 2012;Angoorani and Halabchi 2015;Asr et al 2018;Bordbar et al 2014;Fijan et al 2018;Haerinejad et al 2016;Jalilian et al 2011;Kargarfard et al 2015;Mohammad 2014;Nakhaee et al 2013;Razavi et al 2014;Rezaei 2017;Saeidinejat et al 2017;Sepehri et al 2009;Sobhanian et al 2013), Iraq Habeeb et al 2012), Lebanon Melki et al 2015), Jordan Wazaify et al 2014), Pakistan Uddin et al 2019;Zafar et al 2018), and Sudan (Khidir and Mahmoud 2018); and conference proceedings from Bahrain ) (see Table 2). Correlational study.…”
Section: Resultsmentioning
confidence: 99%
“…Sourcing of AAS was not investigated by more than half of the included studies (Al Allahverdipour et al 2012;Al Nozha and Elshatarat 2017;Alsamani et al 2017;Angoorani and Halabchi 2015;Asr et al 2018;Bahri et al 2017;Bordbar et al 2014;Fijan et al 2018;Jabari et al 2016;Jalilian et al 2011: Karfargard et al, 2015Khullar et al 2016;Khidir and Mahmoud 2018;Melki et al 2015;Mohammad 2014;Razavi et al 2014;Rezaie, 2017;Saeidinejat et al 2017;Zafar et al 2018 Allafi et al 2019;Allahverdipour et al 2012;Al Nozha and Elshatarat 2017;Alsaeed and Alabkal 2015;Althobiti et al 2018;Angoorani and Halabchi 2015;Asr et al 2018;Bahri et al 2017;Hitti et al 2014;Hussain et al 2018;Jalilian et al 2011;Kargarfard et al 2015;Mohammad 2014;Razavi et al 2014;Wazaify et al 2014) reported on the types of AAS and associated drugs being used. The most commonly reported injectable were testosterone and nandrolone decanoate, and the most common oral AAS used were methandrostenolone and stanozolol, with the use of growth hormone reported in only four studies.…”
Section: Aas Regimes Of Use In the Eastern Mediterranean Regionmentioning
confidence: 99%
See 3 more Smart Citations